2022
DOI: 10.3390/v14081700
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Severity and Mortality in Two Pandemic Waves in Poland and Predictors of Poor Outcomes of SARS-CoV-2 Infection in Hospitalized Young Adults

Abstract: SARS-CoV-2 variants pose a significant threat to global public health. However, their influence on disease severity, especially among young adults who may exhibit different clinical characteristics, is debatable. In this retrospective study of 229 young adults hospitalized with COVID-19, we investigated the differences between Poland’s second and third waves of the pandemic. To identify potential predictors of severe COVID-19 in young adults, we analyzed patient characteristics and laboratory findings between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 96 publications
1
7
0
Order By: Relevance
“…These findings were confirmed by Moutchia et al. 100 , 101 and Ziuzia-Januszewska et al 100 , 101 Interestingly, Ziuzia-Januszewska et al. also found that there was no significant difference in mortality between the second and third wave, thereby concluding that Alpha had no effect on disease severity, which was also confirmed by our results.…”
Section: Discussionsupporting
confidence: 92%
“…These findings were confirmed by Moutchia et al. 100 , 101 and Ziuzia-Januszewska et al 100 , 101 Interestingly, Ziuzia-Januszewska et al. also found that there was no significant difference in mortality between the second and third wave, thereby concluding that Alpha had no effect on disease severity, which was also confirmed by our results.…”
Section: Discussionsupporting
confidence: 92%
“…The same results were also obtained in the studies of Ziuzia-Januszewska, et al (2022) and Cunningham, et al (2020), who found no significant age difference in mortality. 12,13 However, young adult patients are still believed to survive better because they have fewer risk factors, such as comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…These results were similar to prior study that showed no significant differences in type 2 diabetes mellitus and hypertension, although the frequency of non-survivors was greater than survivors. 12 Meanwhile, several other studies have shown that the presence of diabetes is strongly associated with the risk of death, the use of mechanical ventilation, and the need for ICU care. Even in young adults, diabetes plays a role as a risk factor for more severe clinical COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 13 studies have been published this year alone (2022) that independently showed that higher NLR in COVID-19 patients entering the hospital was a strong predictor of in-hospital worsening or death [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Chart review showed this to be the case also at our ICU, independently of whether dapsone was given or not.…”
Section: Discussionmentioning
confidence: 99%